Association of Neurofilament Light With the Development and Severity of Parkinson Disease. (31st May 2022) - Halloway, Shannon; Desai, Pankaja; Beck, Todd; Aggarwal, Neelum; Agarwal, Puja; Evans, Denis; Rajan, Kumar B.
Abstract : Background and Objectives: Blood biomarkers may allow earlier identification of Parkinson disease (PD), parkinsonism, and poor PD-related outcomes, such as physical functioning. Neurofilament light (NfL), a neuronal cytoplasmic protein, is a biomarker of neurodegeneration measurable in biofluids. Our objective was to examine the association of serum NfL at baseline with clinically diagnosed PD, parkinsonian signs, and physical functioning change over 16 years in a population-based sample of older adults. Methods: Data came from 1, 327 older participants from the Chicago Health and Aging Project, a longitudinal population-based study. Clinical evaluations included assessing parkinsonian signs in 4 domains—bradykinesia, parkinsonian gait, rigidity, and tremors—using a structured version of the Unified Parkinson's Disease Rating Scale. Board-certified neurologists diagnosed PD. Physical functioning was assessed using chair stands, tandem walk, and timed walk. An ultrasensitive immunoassay was used to measure the concentration of NfL in blood. Results: Of the 1, 254 participants examined for clinical PD, 77 (6.1%) developed clinical PD and parkinsonian signs were on average 9.5 (range 0–66.0). After adjusting for demographic characteristics, APOE ε4 allele, and global cognition, a 2-fold higher concentration of serum NfL was associated with incident clinical PD (odds ratio [OR] 2.54, 95% CI 1.70, 3.81) and global parkinsonian signs (OR 2.44, 95% CI 1.94, 2.94). This association was significant >5 years before diagnosis. Compared with participants with levels below 18.5 pg/mL of serum NfL at baseline, participants with levels between 18.5 and 25.4 pg/mL, between 25.4 and 37.3 pg/mL, and above 37.3 pg/mL had a higher OR of clinical PD at all time intervals from the time of diagnosis to >5 years before diagnosis. A higher concentration of serum NfL was associated with a faster rate of physical functioning decline. In participants with 2-fold higher concentrations of serum NfL, the annual rate of decline in physical functioning increased by 0.15 units (95% CI 0.21, 0.08). Dicussion: Serum NfL was associated with incident clinical PD, parkinsonian signs, and physical functioning decline in a population-based sample. Our findings suggest that NfL may serve as a potential biomarker for neurodegeneration, including PD outcomes. Classification of Evidence: This study provides Class II evidence that serum NfL levels are associated with incident PD, parkinsonian signs, and physical functioning decline.